Aid for trade: Assessing the effects on recipient exports of manufactures and primary commodities to donors and non-donors - Philipp Hühne; Birgit Meyer; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2014)
Considering that primary commodity dependence continues to be a major problem of various lower income countries, we analyze whether Aid for Trade (AfT) has helped recipient countries upgrade and diversify their exports. Estimating an asymmetric and aggregated gravity model, we find that AfT has been effective in promoting recipient exports of manufactures - whereas the effects on primary commodities are typically insignificant. These findings hold not only for trade relations with donor countries but also in south-south trade with other developing countries.
Keywords: F35; F14; 330; aid for trade; recipient exports; export diversification; south-south trade